Pengaruh Brand Awareness dan Desain Produk terhadap Minat Beli Konsumen pada Produk Emas - Acep Samsudin; Rusdi Hidayat; Zefania Mikha Manurung; Aisyah Widya Ayu; Meidya Ayu Prameswari; Restiatin Restiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In the gold jewelry industry, more and more entrepreneurs are offering a variety of brands and designs, and the role of brand awareness and design innovation is important for gold companies, to attract consumers to their products. The purpose of this study was to identify, analyze, and respond to the impact of brand awareness and product design on consumer purchasing decisions for gold products. This makes brand awareness and product design have a positive and significant effect on consumer purchasing decisions on gold products. Keywords: Brand Awareness, Product Design, Purchase Decision.